HUBUNGAN KEMAMPUAN PENGELOLAAN KELAS DAN MOTIVASI MENGAJAR GURU DENGAN AKTIVITAS BELAJAR SISWA DI SEKOLAH DASAR - Maria Kristy Yessy Andminarty; Aloysius Mering; Fadillah Fadillah (Universitas Tanjungpura, 2017)
Abstract The purpose of this research is to get objective information and clarity about the ability of classroom management, teacher motivation and activity of elementary school students Bruder Melati and to know the relationship between the ability of classroom management and teachers motivation with the Bruder Melati Pontianak elementary school students learning activities. The research method used is descriptive method with the form of correlation / relationship studies. The sampling technique used is saturation sampling. The sample in this research is 30 teachers of Bruder Melati Pontianak Elementary School with the characteristics of active teachers and bachelor degree as the minimum requirement. Based on the results of descriptive analysis obtained conclusions (1) Classroom management by teachers in Elementary Bruder Melati Pontianak is 83.20% and classified as Good. (2) The teachers teaching motivation at Bruder Melati Pontianak Elementary School is 84.38% and classified as Good. (3) The student's learning activity at Bruder Melati elementary school is 82.91% and also classified as good. While the results of statistical analysis parametric with simple and multiple linear regression obtained conclusions: (4) There is a positive and significant relationship between the ability of classroom management by teachers with student learning activities. (5) There is a positive and significant relationship between the teachers motivation with student learning activities. (6) There is a significant relationship between the ability of classroom management and teachers motivation with student learning activities simultaneous. Keywords: classroom management, teaching motivation, students learning activities